Urgensi Guru Pendidikan Agama Islam, Guru Bimbingan Konseling dan Wali Kelas dalam Mengatasi Dekadensi Moral - Fitriyah, Eni; Syarief, Nasrul (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
Decadence or moral decline towards students is an increasingly worrying issue in modern society. The moral degradation caused by the various possible consequences that come from outside and within the student. If it is not addressed immediately, then gradually there will be influence on how students will grow and develop.The objective of this study is to find out about moral decadence and how the efforts of teachers in schools, especially teachers of Islamic education (PAI), mentoring teachers, and classmates. The research methods used in this research are qualitative research, phenomenology, data obtained from interviews, observations, documentation. This article also discusses practices and strategies that can be used by teachers of Islamic education, mentoring teachers, and classmates in supporting the formation of strong student character and good morality. Thus, the three-party collaboration is vital in dealing with the challenges of moral decadence in the contemporary era.